SIKAP SOSIAL KEAGAMAAN ROHIS DI SMA PADA DELAPAN KOTA DI INDONESIA - Achmad Habibullah (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
The opinion from studies on religious aspects of senior high school Islamic club summarized in this paper is important considering as lately there is a stronger tendency that Islamic club at school has became a religious movement that is spreading inclusive religious social attitudes. At the beginning of its formation, Islamic club is expected to be the arena for development of Islamic religious knowledge and insight for students that are not sufficiently explored in the activities of Islamic religious education lessons in the classroom. The study used a qualitative approach with in-depth interviews as the main instrument in eight cities in Indonesia, and seeks like to see the social religious attitudes of Islamic club activists associated with aspects of Islam in social life, Islam in the political life of the state, and Islam in gender equality. The findings show that in general high school Islamic club activists are more open and tolerant in neighboring life, but they expect the Islamic system can be the foundation. There is also a tendency that high school Islamic club activists expect that islam can be the foundation of our state system, in which the Islamic system of government (Khilafah Islamiyah) is the best alternative on the democratic system that has drawbacks. High school Islamic club activists in high school tend to put women in a subordinate position of men in both the domestic and the public sphere.